Estimation of Armington elasticities: case of vegetables in Mongolia - Uuld, Amar; Magda, Robert (Applied Studies in Agribusiness and Commerce, 2021)
Mongolian people often consume meat more than vegetable in diet due to traditional nomadic culture. Nowadays, the Mongolian people’s diet has been changing who consume more vegetables with associated urbanization (half of the population live in urban areas, mostly in the capital city). Even though vegetable consumption has been increased recently, the vegetable market is still a high reliance on imports and threatening national food security. Since 2016, the Mongolian government has especially paid attention to increasing vegetable's domestic production and substitution to import vegetables (Ministry of food and Agriculture, 2017). Therefore, this paper provided to substitution elasticity (the Armington elasticity) between import vegetables and domestic vegetables in Mongolia. Additionally, we estimated the home bias value of vegetables. The so-called Armington elasticities are widely used for computable general equilibrium (CGE) analysis, which determines a degree of substitution between import goods and domestically produced goods. Several of the authors studied Armington elasticities at the product level. We choose six vegetables (such as potato, garlic and onion, tomato, carrot and turnips, cabbage, and cucumber) related to lack of information. The empirical result shows that the Armington elasticities in the long-run higher than the short-run with exception of potato which means that products are similar in the long-run. However, our estimated Armington elasticities are quite lower than the previous studies result which means that Mongolian people indicated more prefer home growing vegetables than import vegetables. Moreover, we found that the home bias value is high in the short-run even long -run, this appears to be a higher relative weight on home vegetables.JEL code: F13, Q17, Q18